Reliability-based optimization of direct and indirect LCC of RC bridge elements under coupled fatigue-corrosion deterioration processes. (January 2016) - Saad, L.; Aissani, A.; Chateauneuf, A.; Raphael, W.
Abstract: An optimal bridge design should minimize the life cycle cost ( LCC ) of the structure without compromising its safety. Various cost components need to be evaluated when assessing the life cycle cost of a reinforced concrete bridge. When the structure is subjected to performance degradation due to aging, the probabilistic modeling of degradation is required. In this paper, the reliability-based design optimization RBDO is performed on the life cycle cost of the structure subject to deterioration processes of fatigue and corrosion. This paper advances the state of the art by: considering the coupled corrosion fatigue model in the design optimization and by developing a new approach to evaluate the user delay costs on a bridge, based on direct and indirect costs related to degradation and failure. Also, a sensitivity analysis of optimal costs and design variables is performed. The improved life cycle cost analysis presented herein can be applied to select the optimal design of reinforced concrete bridge elements, by minimizing both agency and bridge user costs, while providing the required safety along the structure lifetime, taking into account the most severe degradation processes. Highlights: Integrating the coupled corrosion fatigue deterioration model in the design optimization. Developing a new approach to evaluate the user delay costs. Proposing equations for different scenarios that may lead to user costs. Estimating the direct and indirect costs related to degradation and failure. Studying the impact of different parameters on optimal solutions.